Distribution of Private Health Expenditure Analysis on Provincial in Thailand - Somjai, Darunwan (Thammasat Review, 2021)
This research analysed the distribution of private health expenditure at the provincial level in Thailand. Health expenditure in each household was categorised into three aspects: medicine and medical supplies, medical expenses from visiting the Out Patient Department (OPD) and In Patient Department (IPD) at hospitals. Panel Data from 77 provinces from 2012 – 2017 was used in this research. The data was analysed using Multiple Regression Analysis and a Fixed Effect Model to round up the parameter. The Hausman Test was used to test the rationality of the model. Inequity in the distribution of household health expenditure per each province was studied using the Lorenz Curve and the Gini Index while equity in the healthcare funding system was investigated using the Kakwani Index. The study found that household medical expenses from visiting the OPD at a hospital was the highest monthly expenditure. For inequity in private health expenditure, the Gini Index showed that the overall health expenditure was 0.36, while the health expenditure in each aspect found that the IPD was highest in inequity in private health expenditure, with the Gini Index equalling 0.49. It was also found that the Gini Index has increased every year. This rise shows that the inequity in private health expenditure is increasing continuously. The Kakwani Index of expenditure equity yielded a negative value. When considering the factors that contribute to the rise of private health expenditure, it was found that the expenditure often increased in parallel to demand. The results of this research also showed that the health service system affected all 3 aspects of the private health expenditure. Universal Health Coverage was the only system that accounted for the increase of private health expenditure in all aspects. On the other hand, the Social Security Scheme reduced the expenditure.